2016
DOI: 10.1016/j.dib.2016.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological data of iron and calcium in the mouse lung after asbestos exposure

Abstract: This data article contains data related to the research article entitled, “Synchrotron X-ray microscopy reveals early calcium and iron interaction with crocidolite fibers in the lung of exposed mice” [1]. Asbestos fibers disrupt iron homeostasis in the human and mouse lung, leading to the deposition of iron (Fe) onto longer asbestos fibers which forms asbestos bodies (AB) [2]. Similar to Fe, calcium (Ca) is also deposited in the coats of the AB. This article presents data on iron and calcium in the mouse lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In vivo and in vitro studies demonstrated that both chrysotile and crocidolite induce oxidative stress and the production of local inflammatory mediators such as cytokines and growth factors. This leads to a reactive microenvironment characterized by inflammation and proliferation of mesothelial cells ultimately inducing MPM or other asbestos-related diseases (Nymark et al 2007;Trevisan et al 2016). Mesothelial cells exposed to crocidolite were reported to have an extensive altered expression of genes involved in integrin-mediated signalling pathways, DNA damage repair, and cell cycle regulation (Acencio et al 2015;Wang et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo and in vitro studies demonstrated that both chrysotile and crocidolite induce oxidative stress and the production of local inflammatory mediators such as cytokines and growth factors. This leads to a reactive microenvironment characterized by inflammation and proliferation of mesothelial cells ultimately inducing MPM or other asbestos-related diseases (Nymark et al 2007;Trevisan et al 2016). Mesothelial cells exposed to crocidolite were reported to have an extensive altered expression of genes involved in integrin-mediated signalling pathways, DNA damage repair, and cell cycle regulation (Acencio et al 2015;Wang et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…40 Chrysotile and crocidolite types of asbestos were shown to induce oxidative stress and induce local inflammatory mediators (cytokines and growth factors), leading to a reactive microenvironment of inflammation and proliferation of cells. 41,42 Exposure of cells to asbestos induces extensive alterations in expression of genes involved in integrinmediated signalling, DNA damage repair, and cell cycle regulation pathways. 43,44 The chronic inflammation caused by exposure of serosal surfaces to asbestos fibres is likely to represent a central factor in the carcinogenesis and is likely to be mediated through epigenetic changes.…”
Section: Asbestos-induced Epigenetic Changes (Figure 1)mentioning
confidence: 99%
“…Previously, cytotoxic effects of asbestos fibres have been investigated both in in vitro cellular models (Casalone et al, 2018), as well as in animal models (Altomare et al, 2005;Trevisan et al, 2016), with reports present from as early as 1970s (Davis, Bolton, & Garrett, 1974). Most studies have investigated the relationship between asbestos exposure, cytotoxicity, and asbestos-induced cellular and molecular alterations on human or animal derived mesothelial cells (Casalone et al, 2018;Kopnin et al, 2004), lung fibroblasts , or macrophages (Nadeau & Lane, 1988).…”
Section: Introduction To the Chaptermentioning
confidence: 99%